Red cell distribution width is associated with future risk of incident stroke - Lappegård, Jostein; Ellingsen, Trygve S.; Skjelbakken, Tove; Mathiesen, Ellisiv B.; Njølstad, Inger; Wilsgaard, Tom; Brox, Jan; Brækkan, Sigrid K.; Hansen, John-Bjarne (Thrombosis and Haemostasis, 2016)
Red cell distribution width (RDW), a measure of the variability in size of the circulating erythrocytes, is associated with cardiovascular morbidity and mortality. We aimed to investigate whether RDW was associated with incident stroke and case fatality in subjects recruited from the general population. Baseline characteristics were obtained from 25,992 subjects participating in the fourth survey of the Tromsø Study, conducted in 1994/95. Incident stroke was registered from inclusion until December 31, 2010. Cox regression models were used to calculate hazard ratios (HR) with 95 % confidence intervals (95 % CI) for stroke, adjusted for age, sex, body mass index, smoking, haemoglobin level, white blood cell count, thrombocyte count, hypertension, total cholesterol, triglycerides, self-reported diabetes, and red blood cell count. During a median follow-up of 15.8 years, 1152 participants experienced a first-ever stroke. A 1 % increment in RDW yielded a 13 % higher risk of stroke (multivariable HR: 1.13, 95 % CI: 1.07–1.20). Subjects with RDW in the highest quintile compared to the lowest had a 37 % higher risk of stroke in multivariable analysis (HR: 1.37, 95 % CI: 1.11–1.69). Subjects with RDW above the 95-percentile had 55 % higher risk of stroke compared to those in the lowest quintile (HR: 1.55, 95 % CI: 1.16–2.06). All risk estimates remained unchanged after exclusion of subjects with anaemia (n=1102). RDW was not associated with increased risk of death within one year or during the entire follow-up after an incident stroke. RDW is associated with incident stroke in a general population, independent of anaemia and traditional atherosclerotic risk factors.
Keywords: Epidemiological studies; stroke; risk factors